The Development of Educational Personnel to Enhance Teaching Efficiency with Digital Technology in Schools Under the Office of Phitsanulok Primary Education Service Area 3 - Phrommeenetr, Somlak; Kayaphad, Sanit; Tengtraisorn, Chukeart; Ketchan, Rat (Journal of Dhamma for Life, 2025)
The objectives of this research were: 1) to study the level of operations for developing educational personnel to enhance the effectiveness of teaching and learning using digital technology, and 2) to compare the operations for developing educational personnel to enhance the effectiveness of teaching and learning using digital technology in schools under the Phitsanulok Primary Education Service Area Office 3 (PESAO 3). The sample group consisted of school administrators and teachers from schools under PESAO 3, calculated using Taro Yamane’s formula, resulting in a total of 487 people. The sample was randomly selected using a convenience sampling method. Data was collected through a questionnaire to study the development of educational personnel for improving the effectiveness of teaching and learning using digital technology. The statistics used for data analysis included frequency, percentage, mean, standard deviation, and hypothesis testing using t-test and F-test. The results of the study found that the organization had a high level of personnel development in ICT, especially in terms of training and sending personnel to study visits. However, team and organizational development had the least progress. The comparison of ICT development in personnel showed that those aged 40 and above, with higher education, higher positions, and more work experience, had more development in ICT than younger individuals with lower education, lower positions, and less work experience. Meanwhile, gender did not affect the level of ICT development in educational personnel. This research provides valuable insights that can be used to propose strategies for organizations to develop personnel in ICT effectively and appropriately. It can help build digital technology skills at all levels of personnel to enhance the efficiency of teaching and learning and the operations of the organization.